Malaysian Stock Price and Macroeconomic Variables: ARDL Bounds Test - Ricky Chee Jiun Chia; Shiok Ye Lim (Kajian Malaysia, 2015)
This study examines the response of the Malaysian stock market on selected macroeconomic variables, namely industrial production, inflation, money supply (M1), interest rate and exchange rate over the period 1980:Q1 to 2011:Q3. By using the autoregressive distributed lag (ARDL) bounds test, this study documented the presence of a long-run relationship between share prices and economic activity. The long-run coefficients suggest that Malaysian share prices are influenced positively by money supply and interest rates, and negatively by inflation. The results from the error correction mechanism indicate that real returns are Granger caused by real money growth and real interest rates. When the exchange rate is included in the estimation, significant relationship has been observed and this implies that exchange rate fluctuations can cause movement in stock prices. This study reveals that the exchange rate is a proper determinant that has explanatory power over stock returns. From the policy perspective, the results suggest that, monetary policies aimed at stabilizing inflation can impact the stock market positively. Since the movement of stock market is highly elastic to inflation, the relationship needs to be taken into account in developing policy for the benefit of the Malaysian economy.